Analysis Of Employee Performance At Ma'had Al Ayman Arabic Language And Islamic Education Foundation - Dani Sudiwan* (Universitas Syiah Kuala, 2023)
In an Islamic Education Foundation, the success and progress obtained cannot be separated from the existing tools, both management systems and employee performance. Many people view the completeness of facilities as the only factor that brings success in the foundation. The employees are only treated as supporting elements and used as workers. Ma'had Al-Ayman Arabic Language and Islamic Education Foundation is one of the Islamic education foundations in Pontianak City that has not maximized the potential of its employees. The study entitled